Cumulative determinants of adolescent health indicators: the effects of social and structural determinants of health and child sexual abuse on overdose and suicide attempt - Deirdre Colburn; Kimberly J. Mitchell; Ateret Gewitz-Meydan (Frontiers in Public Health)
BackgroundResearch has increasingly focused on the role of social and structural determinants of health (SDoH) in shaping behavioral and mental health-related outcomes, including suicide and substance use disorder. While child sexual abuse (CSA) is a well-established risk factor for these outcomes, less is known about the association with image-based sexual abuse (IBSA) and its relationship to suicide and overdose risk. Moreover, limited research has explored the interaction between abuse experiences and SDoH deficits, particularly how cumulative disadvantages may exacerbate these risks.MethodsUsing a sample of young adults aged 18–28 (n = 2,630) recruited through social media, this study examines the links between SDoH deficits and abuse type prior to age 18 (CSA and IBSA) with suicide attempts and overdose outcomes. Participants reported experiences of hands-on CSA, IBSA, or both, along with self-reported deficits in five key SDoH domains: economic stability, social and community context, housing stability, healthcare access, and neighborhood conditions. A cumulative SDoH deficit scale (0 to 4 + deficits) was created to examine the compounding effects of social and structural disadvantage. Logistic regression models were used to assess the association between SDoH deficits, abuse type, and two primary outcomes: suicide attempts and drug overdose prior to age 18 and lifetime.ResultsThe likelihood of each health indicator increased with each additional SDoH deficit reported. The largest percentage-point increase was in lifetime suicide attempt, which was reported by approximately 15.2% of those with 0 SDoH compared to 49.9% of those with 4 or more SDoH deficits. There were also large differences in lifetime suicide attempt by abuse type (20.3% among those with no abuse vs. 60.6% of those with both types). Notably, across each abuse category, the predicted probabilities of suicide attempt, both before age 18 and lifetime, increased with each additional SDoH deficits.DiscussionFindings suggest that CSA and IBSA do not operate in isolation but interact with social and structural determinants in their association with key health indicators. The results highlight the need for holistic prevention and intervention strategies that address both childhood trauma and modifiable SDoH.